Flowback: Federal Regulation of Wastewater from Hydraulic Fracturing - Gaba, Jeffrey M. (Columbia Journal of Environmental Law, 2019)
A variety of production techniques, including hydraulic fracturing (“fracking”), have opened new reserves of natural gas from unconventional sources in the United States. The resulting growth of natural gas production in the last decade has dramatically altered the U.S. energy picture. Increasing supplies of natural gas have lessened reliance on coal for electricity generation, and the United States may be poised to be an exporter of natural gas. This Article addresses issues associated with federal regulation of fracking wastewater under RCRA and the CWA. Part I discusses the fracking process and current federal regulation of the fracking process itself under the Safe Drinking Water Act. Part II addresses the potential adverse environmental impacts of fracking wastewater, as well as the management and disposal options currently employed within the industry. Part III discusses issues associated with EPA’s exclusion of this wastewater from classification as a hazardous waste under RCRA...Part IV addresses regulation of the direct discharge of fracking wastewater to surface water under the Clean Water Act...Finally, Part V discusses issues associated with the regulation of fracking wastewater sent to Publicly Owned Treatment Works (“POTWs”).